The Influence of Delegative Leadership Style, Motivation, Work Environment on Employee Performance in Self-Efficiency Mediation in SNVT Housing Provision of East Java Province - Rohmantika Wulandari; Djawoto Djawoto; Prijati Prijati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aimed to investigate and analyze the effect of delegating leadership style, work motivation, work environment on employee performance mediated by self-efficacy in SNVT Provision of Housing in East Java Province (PNP). The population of this study was all employees of SNVT PNP. The sampling technique used a saturated sample. The data analysis technique was s the path analysis model. As the path analysis test results, this study indicated that (1) the delegative leadership style had an effect on employee performance; (2) the work motivation had an effect on employee performance; and (3) the work environment had an effect on employee performance. Moreover, this study used the Sobel test to present the effect of mediation. The results showed that (1) self-efficacy could mediate delegating leadership style to employee performance; (2) self-efficacy could mediate work motivation on employee performance; (3) self-efficacy could mediate the work environment on employee performance. Furthermore, this study concluded that the variables of delegating leadership style, work motivation, and work environment affect employee performance and could be mediated by the self-efficacy variable.